Aphrodite's sisters - Stylianou-Lambert, Theopisti; Morris, Christine; Papantoniou, Giorgos; Heraclidou, Antigone (My University, 2023)
This paper presents two interrelated art projects - arte-facts and Collecting Aphrodite's Sisters - that explore the multiple social lives of the most popular Cypriot statue of Aphrodite and its copies: the Aphrodite of Soloi, an ancient marble statue of the naked Goddess with missing arms and legs. The two projects presented here bring attention to the current and multiple manifestations of Aphrodite and how her image is experienced by people, both within and beyond Cyprus, in their everyday lives. These perspectives are distinctive from the more official and touristic narratives that have been traditionally associated with Aphrodite in her specifically Cypriot context, although they sometimes respond to or react against these more established narratives. Before introducing and discussing the two art projects, we begin by situating them within a broader historical, archaeological and art historical context, offering a short discussion of Aphrodite as a key cultural symbol of the island, and then turning the focus onto the ancient statue which has provided the inspiration for the two projects.